Antibodies to co-trimoxazole (trimethoprim and/or sulfamethoxazole) related to the presence of the drug in a commercial low-ionic-strength solution - Pham, Bach-Nga; Gien, Dominique; Bensaad, Farid; Babinet, Jérome; Dubeaux, Isabelle; Rouger, Philippe; Pennec, Pierre-Yves Le (Transfusion (Philadelphia, Pa.), 2012)
BACKGROUND: Drug‐dependent antibodies have been associated with approximately 10% of acquired immune hemolytic anemia cases. These antibodies are a rare cause of interference in pretransfusion red blood cell (RBC) serologic testing. The aim of this work was to report three cases of subjects developing antibodies against co‐trimoxazole, a combination of trimethoprim (TMP) and sulfamethoxazole (SMX). CASE REPORT AND METHODS: Blood samples of donor/patients were referred to our laboratory for the exploration of a positive antibody detection test. There was no recent history of drug taking. Antibody identification was performed by gel test using an indirect antiglobulin test, with reagent RBCs in low‐ionic‐strength solutions (LISS) containing co‐trimoxazole or not. RESULTS: All three sera showed positive reactions when RBCs were resuspended in LISS containing co‐trimoxazole, but negative reactions when RBCs were resuspended in LISS without antibiotic. We detected antibodies against co‐trimoxazole showing three different antibody patterns: anti‐TMP plus anti‐SMX, anti‐TMP alone, or anti‐SMX alone. Anti‐TMP showed an apparent anti‐Ku specificity in the two cases where it was present. Anti‐SMX showed an apparent anti‐H specificity in one of the two cases described. The drug‐dependent antibodies were not associated with acquired hemolytic anemia or other pathologies. CONCLUSION: Antibodies against co‐trimoxazole may only be detected when using a diluent for reagent RBCs containing the drug in question. Antibody pattern (anti‐TMP and/or anti‐SMX) may vary according to individuals' immune response. Drug‐dependent antibodies may react as antibodies against a high‐prevalence antigen, supporting the hypothesis of antibodies to drug and membrane components. Drug‐dependent antibodies such as anti‐co‐trimoxazole may be a serologic finding without clinical features.